Rekonstruksi Paradigma Transfer of Sentenced Persons: Antara Kepentingan Narapidana dan Kepentingan Negara, serta Implikasinya pada Tata Kelola Transfer of Sentenced Person - Arsil, Fitra (UI Scholars Hub, 2025)
This article analyzes the paradigm shift in the Transfer of Sentenced Persons (TSP) from a regime oriented towards the rehabilitation and social reintegration of prisoners to a new configuration increasingly driven by state interests, such as national security, prison population management, immigration policy, budget efficiency, diplomatic calculations, and human rights image. Based on a legal-normative approach combined with institutional analysis and a comparison of practices in various jurisdictions, this paper shows how the principle of consensualism, initially interpreted as